Capacity Analysis of Degrees of Saturation of Traffic Transportation (Signalized Intersection of Road Gajah Mada - Munginsidi And Railway Bojonegoro) - Herta Novianto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Gajah Mada Road and Munginsidi Road in the Bojonegoro district are important roads for the local community. The existence of these various necessary facilities and means will have an impact on the relatively dense traffic volume. Based on the review of the study location and the results of the survey as well as the data collection and processing carried out, the following research results were obtained: The capacity of the Monginsidi Road section is 1,185.52 PCU/hour with a degree of saturation of 0.59, while on the Gajah Mada Road section the capacity of the section roads amounted to 2,836.78 PCU/hour with a degree of saturation of 0.79. Traffic flow performance is determined by the level of road service, the road service level is classified as level C with the description that the flow is stable, but vehicle speed and movement are controlled. On the Gajah Mada Road section, the road service level is classified as level D with the description that the flow is approaching unstable, speed can still be controlled, and Q/Can still be tolerated. To create effective and efficient conditions, namely the realization of orderly, smooth, and comfortable traffic flow, there must be a balance between facilities and facility users so that various traffic problems can be resolved as early as possible.